Interactive design in enhancing user experience in museum / Romiza Md Nor and Muhammad Hafizuddin Abdul Razak - Md Nor, Romiza; Abdul Razak, Muhammad Hafizuddin (UiTM Cawangan Perlis, 2021)
A museum can be a suitable context to experiment with a new interaction technique which guiding visitors and improving their experience for a successful learning environment also to enrich user experience. Mobile technology is used to enhance user experience in a cultural environment that offers more information than physically exposed technology. Therefore, the introduction of augmented reality (AR) that allow visitor to experience interaction in a way that increased knowledge, learning and give additional information with any artefact exhibitions they interact in the museum is applied in this project. The objectives of this research are to develop an interactive design in enhancing user experience in artefact display and evaluate user experience. ADDIE Model is applied as the methodology that consists of five phases which are analysis, design, development, implementation, and evaluation. Principles of Interactive Design is utilized in designing the mobile AR application and developed using Unity, Blender and Vuforia. User Experience evaluation method is conducted where findings shows that most respondents are satisfied, and usage of mobile AR has enhanced their experience through navigation during museum visit that also give a lot of new insight on historical artefact that being displayed.